Primary oral manifestation of Langerhans cell histiocytosis refractory to conventional therapy but susceptible to BRAF-specific treatment: a case report and review of the literature. (October 2019) - Neckel, Norbert; Lissat, Andrej; von Stackelberg, Arendt; Thieme, Nadine; Doueiri, Mohemed-Salim; Spors, Birgit; Beck-Broichsitter, Benedicta; Heiland, Max; Raguse, Jan-Dirk
Langerhans cell histiocytosis (LCH) is a diagnostic and therapeutic challenge. We report on a rare case of its primary oral manifestation that was treated successfully with the BRAF-specific agent, vemurafenib, after insufficient standard LCH treatment. This case underlines the importance of proper diagnosis and the evaluation of targeted therapy as a valuable tool in LCH treatment. Furthermore, the close collaboration of surgeons, oncologists, and dentists is mandatory to ensure adequate treatment, restore the stomatognathic system in debilitating post-treatment situations, improve quality of life, and ensure effective disease control in infants and young patients.